The Effectiveness of the Demonstration Method to Improve Students’ Writing Skills Procedural Texts assisted by Canva: Tenth Grade Students of MA An-Nur Cikalongwetan - Euis Widiasari; Dasep Suprijadi; Efransyah (PROJECT (Professional Journal of English Education), 2026)
This study aims to evaluate how effective the Canva-backed demonstration method is at enhancing the students' procedural text writing abilities, while also outlining how it is applied and uncovering the challenges students face. A mixed-methods framework incorporating a sequential explanatory strategy was deployed in this investigation. The participants of this study were 40 tenth-grade students of MA An-Nur Cikalongwetan. The quantitative data were collected through pre-test and post-test, while the qualitative data were obtained from classroom observation and questionnaires. The findings based on the quantitive data revealed a significant improvement in the students’ writing performance, as indicated by the increase in the mean score from 65 in the pre-test to 78 in the post-test. Outcomes from the paired sample t-test yielded a p-value below 0.05, confirming that the intervention led to a statistically significant shift in outcomes. Meanwhile, classroom observations demonstrated gradual improvement in students’ participation and engagement, while questionnaire results indicated that the integration of the demonstration method and Canva positively supported the students’ learning. However, some difficulties remained, particularly in grammar, organization of ideas, and confidence. Overall, the demonstration method assisted by Canva is effective in improving the students’ writing skills and promoting active learning.